2005
DOI: 10.1128/aem.71.12.7781-7787.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersion Solutions Containing Enterocin AS-48 on Listeria monocytogenes in Vegetable Foods

Abstract: The effect of immersion solutions containing enterocin AS-48 alone or in combination with chemical preservatives on survival and proliferation of Listeria monocytogenes CECT 4032 inoculated on fresh alfalfa sprouts, soybean sprouts, and green asparagus was tested. Immersion treatments (5 min at room temperature) with AS-48 solutions (25 g/ml) reduced listeria counts of artificially contaminated alfalfa and soybean sprouts by approximately 2.0 to 2.4 log CFU/g compared to a control immersion treatment in distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 44 publications
1
47
0
3
Order By: Relevance
“…The cell suspensions were transferred to sterile eppendorf tubes, (LIN et al, 2000). Other sanitizers studied for their effectiveness in removing pathogens from fresh fruit and vegetables include trisodium phosphate (ZHUANG; BEUCHAT, 1996, WEBER;OBRIEN;BENDER, 2004;MOLINOS et al, 2005), organic acids (PIROVANI et al, 1998;RHEE et al, 2003;BJORNSDOTTIR;BREIDT;McFEETERS, 2006), hydrogen peroxide (BRENNAN; PORT; GORMLEY, 2000), and ozone (KOSEKI et al, 2001;ACHEN;YOUSEF, 2001;BELTRAN et al, 2005). Although various sanitizers have been examined for their effectiveness, most treatments have been shown to have minimal effects, resulting in less than a 2 log cfu.g -1 (cm 2 ) reduction in bacterial numbers, and most would not be suitable products for use at the household level (BEUCHAT et al, 1998).…”
Section: Antimicrobial Effects Of Vinegar and Lemon Juice Against Indmentioning
confidence: 99%
“…The cell suspensions were transferred to sterile eppendorf tubes, (LIN et al, 2000). Other sanitizers studied for their effectiveness in removing pathogens from fresh fruit and vegetables include trisodium phosphate (ZHUANG; BEUCHAT, 1996, WEBER;OBRIEN;BENDER, 2004;MOLINOS et al, 2005), organic acids (PIROVANI et al, 1998;RHEE et al, 2003;BJORNSDOTTIR;BREIDT;McFEETERS, 2006), hydrogen peroxide (BRENNAN; PORT; GORMLEY, 2000), and ozone (KOSEKI et al, 2001;ACHEN;YOUSEF, 2001;BELTRAN et al, 2005). Although various sanitizers have been examined for their effectiveness, most treatments have been shown to have minimal effects, resulting in less than a 2 log cfu.g -1 (cm 2 ) reduction in bacterial numbers, and most would not be suitable products for use at the household level (BEUCHAT et al, 1998).…”
Section: Antimicrobial Effects Of Vinegar and Lemon Juice Against Indmentioning
confidence: 99%
“…Nevertheless, for both alfalfa and soybean sprouts, the bacteriocin concentrations of 12.5 as well as 25 µg/ml reduced the concentrations of viable listeria below the detection levels from day 1 to day 7 of storage at temperatures of 6ºC as well as 15ºC. These results indicated that residual bacteriocin adsorbed to the treated sprouts was able to provide a protective effect after treatment for samples stored under a broad interval of refrigeration temperatures (Cobo Molinos et al, 2005). Nevertheless, incubation of the treated samples at a higher temperature of 22ºC seriously compromised the protective effect of the bacteriocin.…”
Section: Treatment With Bacteriocin Preparationsmentioning
confidence: 52%
“…Because of its broad spectrum of inhibition and increased stability due to its cyclic structure, enterocin AS-48 can be a sound candidate for decontamination of vegetable foods containing L. monocytogenes and other foodborne bacteria sensitive to this bacteriocin. In experiments carried out for enterocin AS-48 on sprouts, L. monocytogenes was able to grow without bacteriocin on alfalfa and soybean sprouts and in green asparagus at temperatures of 6 to 22ºC and to reach high cell numbers (up to 6 log CFU/g, depending on temperature) during storage (Cobo Molinos et al, 2005). Sprouts inoculated with L. monocytogenes were treated by immersion for 5 min in distilled water or in bacteriocin solutions of 5, 12.5, and 25 µg/ml.…”
Section: Treatment With Bacteriocin Preparationsmentioning
confidence: 99%
See 2 more Smart Citations